2015
DOI: 10.1002/joc.4250
|View full text |Cite
|
Sign up to set email alerts
|

A new methodology for identifying daughter cyclogenesis: application for the Mediterranean Basin

Abstract: This study is the first one to objectively identify ‘parent–daughter’ relationships between cyclones and to apply it to Mediterranean cyclones (MCs). The methodology includes cyclone detection, tracking and mapping the area of influence of a cyclone; here daughter cyclones are expected to be found. Cyclone detection and tracking is based on standard algorithms, which were modified to cope with irregularities in intensity and trajectory shapes of MCs. We have developed our own algorithm for mapping cyclones' ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 41 publications
1
43
0
Order By: Relevance
“…Most of the annual precipitation is obtained during a limited number of rain days. The rainy events are typically associated with intrusions of cold air masses from European origin that cross the relatively warm Mediterranean Sea, associated with the Cyprus Lows (Alpert et al, 1990;Saaroni et al, 2010;Ziv et al, 2015). Penetration of warm humid masses originating from tropical Atlantic and/or equatorial regions of Eastern Africa and Arabian Sea contribute as well to rain events, mostly severe ones (Krichak et al, 2004(Krichak et al, , 2015Shalev et al, 2011;De Vries et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the annual precipitation is obtained during a limited number of rain days. The rainy events are typically associated with intrusions of cold air masses from European origin that cross the relatively warm Mediterranean Sea, associated with the Cyprus Lows (Alpert et al, 1990;Saaroni et al, 2010;Ziv et al, 2015). Penetration of warm humid masses originating from tropical Atlantic and/or equatorial regions of Eastern Africa and Arabian Sea contribute as well to rain events, mostly severe ones (Krichak et al, 2004(Krichak et al, , 2015Shalev et al, 2011;De Vries et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Figure (a) displays a composite map of DCs formed over the Gulf of Genoa, on the cold front located east of the parent. The map reflects the well‐known features of Genoa low genesis (see Figure (b) in Buzzi and Tibaldi, and Figure 8(a) in Ziv et al , ). Each DC is formed behind its parent, within the northwesterly flow which is perpendicular to the mountain barrier responsible for the Lee effect.…”
Section: Resultsmentioning
confidence: 72%
“…The study period includes the winter seasons December‐February (DJF) during 33 years, between 1979–1980 and 2011–2012. We have used the database of the cyclones archive (Ziv et al , ), which was derived from the ERA‐Interim reanalysis (Uppala et al , ; European Centre for Medium‐Range Weather Forecasts, ; Dee et al , ), with 6‐h temporal resolution and 0.75° × 0.75° spatial resolution. This archive contains all DCs with life duration greater or equal to 24 h, and details of the parent of each cyclone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The region's climate is intensely affected by external forcing of both mid-latitude and tropical origins (e.g., Alpert et al, 2005). However, the rain in the Mediterranean part of Israel results mainly from passage or development of extratropical cyclones over the eastern Mediterranean, known as the Cyprus Lows (HMSO, 1962;Sharon and Kutiel, 1986;Alpert et al, 1990;Shay-El and Alpert, 1991;Trigo et al, 1999;Schädler and Sasse, 2006;Ziv et al, 2006Ziv et al, , 2015. Saaroni et al (2010a) found that the average contribution of Cyprus Lows to the rainfall in Israel is 83%.…”
Section: Introductionmentioning
confidence: 99%